2013
DOI: 10.4021/ijcp100e
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Saturation Profile in Healthy Term Neonates in the Immediate Post Natal Period

Abstract: Background: A neonate undergoes major physiologic changes during transition from intrauterine to extrauterine period. The percentage saturation of hemoglobin takes about 10 minutes to reach a level of more than 90%. This fact is to be borne in mind while resuscitating a newborn with oxygen to avoid its toxicity. It is still unclear whether the oxygen saturation profile could be affected by racial/ethnic variation, birth weight, sex, APGAR score or maternal factors (age, hemoglobin, type of labor) in term healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…It could be because that they are the commonest pediatric age group who are affected by respiratory disorders. Male predominance of 55% among samples is also observed by other studies -Tiwari et al [8] (52%), LeCleir et al [9] (57%) and Ramachandran et al [7] (73%), all of which have not shown any statistical significance.…”
Section: Discussionsupporting
confidence: 69%
“…It could be because that they are the commonest pediatric age group who are affected by respiratory disorders. Male predominance of 55% among samples is also observed by other studies -Tiwari et al [8] (52%), LeCleir et al [9] (57%) and Ramachandran et al [7] (73%), all of which have not shown any statistical significance.…”
Section: Discussionsupporting
confidence: 69%
“…Several studies from India and other countries have reported SpO 2 and HR values in term newborns after birth, mostly following ECC practice. [36][37][38][39][40] A study in Netherlands newborns documented higher median SpO 2 values for the initial 3 minutes with DCC practice compared with references from Australia/Spain with ECC practice, but the 10th percentile values were higher for the initial 5 minutes. 20,32 The HR values among the Netherland newborns with DCC practices were lower than the Australian/Spanish newborns.…”
Section: Discussionmentioning
confidence: 93%
“…To reduce the toxic effects associated with both to hypoxia and hyperoxia, furthermore in consideration of the data provided by the latest studies, the American Heart Association (AHA) updated guidelines for optimal management of oxygen during resuscitation. AHA stated that room air (21% oxygen) should be used to initiate resuscitation in term and late preterm neonates and that a lower oxygen concentration (21–30%) is recommended to initiate resuscitation of preterm neonates (<35 weeks’ gestation) [ 101 ].…”
Section: Discussionmentioning
confidence: 99%